Meiofauna metabarcoding in Lima estuary (Portugal) suggests high taxon replacement within a background of network stability - Fais, M. (2020)
Meiofauna organisms play an important role in ecological and sedimentary processes in estuarine ecosystems. Recently, the application of environmental DNA (eDNA) for investigating meiofauna in different environments, improved the accessibility to its diversity and composition in a scale, frequency and depth previously unattainable. Nevertheless, little attention has been given to the description of baseline patterns of coupled spatial and temporal dynamics of meiobenthic communities. In an earlier study conducted in Lima estuary (NW Portugal), using eDNA metabarcoding of sediment samples, high levels of meiofauna Operational Taxonomic Units (OTUs) turnover were recorded, between sampling points only a few metres apart, and among sampling stations along the estuary. In order to verify the consistency of these patterns, in the current study we re-assessed Lima estuary's meiofauna communities approximately 1 year after, applying the same methodological approach (targeting segments of the COI and 18S rRNA genes), and expanding HTS-data analyses through the use of association networks. A high degree of spatial turnover was found both within and between sampling stations and this was consistent for both markers and years. As a consequence, most of the beta-diversity was accounted by OTU replacement with only a minor contribution from OTU richness. Despite the high levels of OTU replacement, relatively stable network properties were found in meiofaunal communities, irrespective of the sampled year. Network properties appear to shift sharply from the downstream/high salinity area of the estuary to the mesohaline medium-upstream areas, suggesting high resilience and redundancy of meiofaunal communities along the estuarine gradient. The recognition of meiofauna's networks features may improve the understanding of the ecology and dynamics of these communities that apparently hold large portions of variable elements, thereby making difficult their analyses solely based on the OTU/species composition.